Peningkatan Nilai Gizi Bubur Jagung Tradisional Dengan Fortifikasi Daun Salam - Devifatresia Udjulu , Sri; Adam, Budiyanto; Puspasari , Ifa; Nurmawati, Ardika; Yusuf, Andre (Jurnal Gizi dan Kuliner, 2024)
Traditional food refers to dishes with distinctive flavors commonly consumed by local communities. Some traditional foods in Indonesia use corn as a primary ingredient, such as corn porridge. This article aims to theoretically review the effects of adding bay leaf extract to corn porridge. The data collection method employed in this study is through primary data collection via literature review. The findings indicate that bay leaves have the potential to be used as fortification ingredients to enhance the nutritional value of corn porridge. Bay leaves contain flavonoid compounds acting as natural antioxidants. After fortification with bay leaf extract, corn porridge is then transformed into an instant form using the pregelatinization method. Pregelatinization is influenced by the gelatinization temperature of the ingredients, which varies depending on the type of starch used. Each ingredient requires different time and precise water proportions to achieve optimal gelatinization temperatures.